Dominants of the Present: World Zionism and World Regress. is there Hope for a Positive Future? (London Journal of Research In Humanities and Social Sciences, 2025)
A compact article touches upon the expansion of the world Zionist movement at the present moment. Primary attention has focused on the relationship between this phenomenon and the next advent of the neoconservative state course by name of Trump in the USA. Further, the author reveals the main attributes of the coordinated Zionists policy to achieve Power in many countries. Based on these realities, the necessary solutions are outlined to curb the global Zionist expansion in the fairly near future due to the implementation of a positive scenario for world development.
Keywords: Human Rights; Cultural relativism; Human rights watch; Inherited; Male guardianship; Al Shafallah.; justice.; Justice Administration; Courts of First Instance; Court Organisation; Judicial Institution; Integration; Pedagogy; Generative Artificial Intelligence (GenAI); posthumanist; Generation Z; Quality of Employment IMCE; Intergenerational Precariousness; Decent Work.; alter ego; alter identicus; diagnosis by discrimination; diagnosis by accumulation; ADI-R; ADOS; neuroconstructivist developmental hypothesis.; sustainable development; world zionism; world regress; neoconservative state course; future progress